1993
DOI: 10.1161/01.str.24.5.670
|View full text |Cite
|
Sign up to set email alerts
|

Reactivity of cerebral blood flow to carbon dioxide in various types of ischemic cerebrovascular disease: evaluation by the transcranial Doppler method.

Abstract: The response of cerebral blood flow to changes in the arterial carbon dioxide partial pressure (i.e., carbon dioxide reactivity) has been evaluated as a parameter of cerebral perfusion reserve in patients with cerebrovascular disease. In this study, variations in this reactivity in various ischemic cerebrovascular diseases were evaluated by a newly established method, a transcranial Doppler technique. Thirty-three patients with symptomatic cerebrovascular disease, 13 patients with asymptomatic cerebr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
67
0
1

Year Published

1996
1996
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(74 citation statements)
references
References 26 publications
6
67
0
1
Order By: Relevance
“…35 For the cerebral comparisons, we used the test results from the asymptomatic side of the brain, because vascular reactivity was reduced in ipsilateral versus contralateral arteries in patients with cortical stroke due to tissue damage resulting from the stroke (Table). Although individual studies showed differences in endothelial function between patients with lacunar stroke and those with cortical stroke, 35,37,38,42,44 the combined data showed no difference in vascular reactivity between lacunar and cortical stroke in either cerebral (SMD Ϫ0.29, 95% CI Ϫ0.69 to 0.11, Pϭ0.16) or in peripheral (SMD Ϫ0.23, 95% CI Ϫ0.55 to 0.08, Pϭ0.15) circulation. There was no significant heterogeneity between studies.…”
Section: Lacunar Versus Cortical Ischemic Strokementioning
confidence: 83%
See 1 more Smart Citation
“…35 For the cerebral comparisons, we used the test results from the asymptomatic side of the brain, because vascular reactivity was reduced in ipsilateral versus contralateral arteries in patients with cortical stroke due to tissue damage resulting from the stroke (Table). Although individual studies showed differences in endothelial function between patients with lacunar stroke and those with cortical stroke, 35,37,38,42,44 the combined data showed no difference in vascular reactivity between lacunar and cortical stroke in either cerebral (SMD Ϫ0.29, 95% CI Ϫ0.69 to 0.11, Pϭ0.16) or in peripheral (SMD Ϫ0.23, 95% CI Ϫ0.55 to 0.08, Pϭ0.15) circulation. There was no significant heterogeneity between studies.…”
Section: Lacunar Versus Cortical Ischemic Strokementioning
confidence: 83%
“…30,32,39,40,42 Three studies recruited age-and risk-factor matched control subjects (with longstanding hypertension and hypercholesterolemia in 2 32,34 ; with hypertension only in 1 43 ). Five papers compared patients with lacunar ischemic stroke with patients with cortical ischemic stroke, 35,37,38,42,44 confirming the infarct subtype with CT or MRI. Four studies included patients with Ͼ1 lacunar infarct on CT, 30,37,40,45 MR, 40,45 or both.…”
Section: Characteristics Of Included Patients and Control Subjectsmentioning
confidence: 99%
“…16,17 One of the possible causes of increased postoperative neurologic deficits in diabetic patients is impaired cerebrovascular circulatory and vasodilatory reserve. 18,19 Hyperglycemia leads to impaired vascular function by altering endothelial cell function. The pathway that appears most affected by DM is that of nitric oxide 20 and CPB might alter the cerebral endothelial function more extensively in diabetic patients than in non-diabetic patients.…”
Section: Discussionmentioning
confidence: 99%
“…Altered vascular reactivity associated with atherosclerotic disease in patients has been attributed to hypercholesterolemiainduced 'endothelial dysfunction,' which is characterized specifically by a decrease in the bioavailability of the vasodilator endothelium-derived nitric oxide (NO) (Casino et al, 1993). This view, that endothelial vasodilator NO production is reduced in stroke, is supported by observations that patients with ischemic stroke have impaired cerebral blood flow (Maeda et al, 1993), an effect that is predictive of lacunar infarction (Molina et al, 1999) and is associated with a higher risk of stroke (Yonas et al, 1993). In addition, recent work suggests that reduced capacity to generate NO, reflected by decreased levels of the metabolites of NO in plasma, correlates with risk of stroke (Rashid et al, 2003) and may be due to the presence of specific genetic polymorphisms in the endothelial form of the NO synthase enzyme, eNOS, gene (Tao and Chen, 2009).…”
Section: Introductionmentioning
confidence: 99%